Yearnings & Signals Nederlands Dans Theater at the Edinburgh Festival - Brennan, Mary (Dance Books Ltd., Alton,Hampshire (UK), 2006)
Nederlands Dans Theater at the Edinburgh Festival. PALABRAS CLAVE: Nederlands Dans Theater, Edinburgh Festival, NDT1, NDT2, NDT3, Sir Brian McMaster, Paul Lightfoot, Sol Leon.